Analisis Semiotika Pesan Moral Iklan Layanan Masyarakat Perilaku Konsumtif di Kanal Youtube Bagas Dwi Rizqi - Muaradhyka, Tri Agung; Hamzah Lubis, Faizal (Jurnal Psikotes, 2024)
Social marketing is a form of marketing created to address various social issues in society. Basically, social marketing has the same principles as commercial marketing in general. Both are forms of persuasive communication programs, where commercial marketing aims to gain financial profits, while social marketing aims to shape changes in behavior, both individuals, groups and social order. Researchers will further explore the moral message content of Consumer Behavior Public Service Advertisements contained in Bagas Dwi Rizqi Hidayat's YouTube content in a content analysis review. The theories used are mass media theory, analysis theory, moral messages, messages, morals, public service advertising theory, advertising, consumer behavior, factors causing consumer behavior, social media, YouTube, semiotic theory, Roland Barthes semiotics. The type of research taken by researchers is descriptive qualitative. The research data collection stage is carrying out the process of observation, documentation and literature research, data reduction results, formulating the problem, presenting the data, which is analyzed by the researcher until the stage of drawing conclusions. The author took five scenes to fulfill the needs of research conducted by researchers based on Roland Barthes' semiotic analysis which emphasizes the search for meaning of denotation, connotation and myth. Based on the results of this research, the researcher concluded that the Public Service Advertisement "Consumptive Behavior" directly describes events in society, especially the behavior of Indonesian people in shopping to the point of ignoring their own needs.